Interactive Multimedia as Innovation Islamic Religious Education Learning in Increase Understanding Moderation Religious Based on SDGs 4: Quality Education - Ahmad Safi'ie Hadi; Sucipto Sucipto; Muhajir Muhajir; Fiena Saadatul Ummah; Abdul Wafi; Fatma Fatma (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
Educational transformation in the digital era demands existence innovation aligned learning with the goal of Sustainable Development Goals (SDGs) 4, namely education quality. The world of education, including Islamic Religious Education, must adapt with a more learning model contextual, interactive, and collaborative because progress technology 21st century. Research This aim for describe implementation interactive multimedia- based Islamic Education learning in increase understanding moderation religious student as well as analyze the impact to achieving quality education. Research methods use approach qualitative with design studies case. Data collected through interview with teachers, students, and principal school; observation of the learning process, as well as analysis document supporters. Triangulation sources and methods used guard data validity. Research results show that using interactive media in Islamic Education learning improves involvement cognitive, affective, psychomotor, and spiritual aspects of students. Students more believe self-motivated, enthusiastic, and active in conversations and presentations. Visualization of worship through videos, animations, and simulations help people more understand draft religious moderation and internalization principle like tolerance, togetherness, and responsibility answer social.